Factors associated with pain and disability reduction following exercise interventions in chronic whiplash. (29th May 2015) - Ludvigsson, M. L.; Peterson, G.; Dedering, Å.; Falla, D.; Peolsson, A.
Abstract: Background: Some studies support the prescription of exercise for people with whiplash‐associated disorders (WAD); however, the response is highly variable. Further research is necessary to identify factors which predict response. Methods: This is a secondary analysis of a randomized, multicentre controlled clinical trial of 202 volunteers with chronic WAD (grades 2 and 3). They received either neck‐specific exercise with, or without a behavioural approach, or prescription of physical activity for 12 weeks. Treatment response, defined as a clinical important reduction in pain or disability, was registered after 3 and 12 months, and factors associated with treatment response were explored using logistic regression. Results: Participation in the neck‐specific exercise group was the only significant factor associated with both neck pain and neck disability reduction both at 3 and 12 months. Patients in this group had up to 5.3 times higher odds of disability reduction and 3.9 times higher odds of pain reduction compared to those in the physical activity group. Different baseline features were identified as predictors of response depending on the time point examined and the outcome measure selected (pain vs. disability). Conclusion: Factors associated with treatment response after exercise interventions differ in the short and long term and differ depending on whether neck pain or disability is considered as the primary outcome. Participation in a neck‐specific exercise intervention, in contrast to general physical activity, was the only factor that consistently indicated higher odds of treatment success. These results support the prescription of neck‐specific exercise for individuals with chronic WAD.